NILAI MODERASI BERAGAMA DALAM SEMBOYAN TANA TORAJA: MISA KADA DIPOTUO, PANTAN KADA DIPOMATE - Resi (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Tana Toraja is inhabited by multicultural societies consisting of various ethnic and religious backgrounds. The tolerance embedded in the Toraja community is the key to peace in an environment without discrimination. This research focuses on Tana Toraja's value of tolerance for religious life in the midst of diversity. The Toraja community is a plural society in terms of religion because it is dominated by Christianity as a majority. This reality is a wealth but also a potential inter-religious conflict. Therefore, the prayer that continues to live in the Toraja people's lives, the Mass kada dipotuo, the ex-Kada dipomate is the key to the peace that is secured for the life of the Tóraja people due to the family and emotional bonds. This study uses a type of library research, which is a series of data gathering on books and reference journals that discuss the same issues related to the value of religious moderation in Tana Toraja: misa kada dipotuo, pantan kada dipomate. The results of this study, is to study how the history and philosophy of Tana toraja and how cultivation of the religious moderators in the Tana Toraj: missa kada Dipotuo.